(untitled) (World Bulletin of Social Sciences, 2025)
This article analyzes the importance of social media marketing (SMM) in the development of content strategies in online journalism. In today’s digital environment, social networks have become a key tool for attracting audiences and disseminating information. The article examines methods of delivering content to target audiences through SMM, strategies for increasing its popularity, and enhancing user engagement.